1996
DOI: 10.1002/etc.5620151104
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen limitations and aging as explanations for the field persistence of naphthalene in coal tar‐contaminated surface sediments

Abstract: Abstract-Naphthalene has been transported approx. 400 m via groundwater flow from buried subsurface coal tar to an organic matter-rich seep area where the water emerges at the foot of a hill in a field study site. We have tested several hypotheses for explaining why naphthalene persists in seep sediments. In aerobic laboratory flask assays, conversion of 14 C-naphthalene to 14 CO 2 occurred and was not stimulated by amendments with vitamins or inorganic nutrients. Thus, neither toxicity nor nutrient limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
(38 reference statements)
1
33
0
Order By: Relevance
“…6, 20, and 21). To discover the identity of the active populations, we implemented field respiration and SIP procedures (19), which released 13 C-labeled naphthalene where flowing groundwater has deposited naphthalene in organic matter-rich surface sediment (22). The small volumes of naphthalene-dosed sediment (Ϸ50 ml) were covered by open-bottom glass chambers that allowed headspace gases produced by the native microbial community to be periodically gathered and analyzed for evolution of 13 CO 2 above background produced from sediment organic matter (19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6, 20, and 21). To discover the identity of the active populations, we implemented field respiration and SIP procedures (19), which released 13 C-labeled naphthalene where flowing groundwater has deposited naphthalene in organic matter-rich surface sediment (22). The small volumes of naphthalene-dosed sediment (Ϸ50 ml) were covered by open-bottom glass chambers that allowed headspace gases produced by the native microbial community to be periodically gathered and analyzed for evolution of 13 CO 2 above background produced from sediment organic matter (19).…”
Section: Resultsmentioning
confidence: 99%
“…If a high-substrate concentration had been used, SIP may have revealed opportunistic microorganisms other than those active under ambient site conditions. Because the mass of 13 C-naphthalene added (Ϸ60 g͞5 g sediment) roughly matched ambient concentrations (22), we feel that potential concentration-based artifacts were avoided. Data interpretation presumed that the 16S rRNA gene sequences found in 13 C-labeled DNA were indicative of microbial populations directly responsible for naphthalene biodegradation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chemotaxis has been proposed to have an impact on the fate of contaminants in the environment (Pandey and Jain, 2002;Parales and Harwood, 2002), but the availability of dissolved oxygen can be limited at contaminated sites (Madsen et al, 1996). Here, we have shown that low dissolved oxygen concentrations and aerotaxis can inhibit chemotaxis to naphthalene and, consequently, the rate of naphthalene degradation under aerobic conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Characteristics and details of this site have been previously published (24)(25)(26)(27)42). Naphthalene-degrading strains isolated from contaminated sediment from our study site (designated Cg) have been previously described (19).…”
mentioning
confidence: 99%